2012
DOI: 10.1007/s00167-012-1880-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anterior and rotatory laxity using navigation between single- and double-bundle ACL reconstruction: prospective randomized trial

Abstract: Prospective comparative study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 45 publications
4
103
0
1
Order By: Relevance
“…IKDC score in our study was found to be comparable to that in other studies. 5,23,[28][29][30][31]34 According to the table, all functional scores in our study fall in the range as that of the previous studies ( Table 1). Range of motion of knee joint was normal in 24 (96%) patients at the end of 4 years.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…IKDC score in our study was found to be comparable to that in other studies. 5,23,[28][29][30][31]34 According to the table, all functional scores in our study fall in the range as that of the previous studies ( Table 1). Range of motion of knee joint was normal in 24 (96%) patients at the end of 4 years.…”
Section: Discussionmentioning
confidence: 55%
“…Pivot shift test was evaluated in 12 studies with a total 488 patients. 6,22,24,[28][29][30] 16 From our experience with the DB ACL reconstruction technique, we can conclude that DB ACL reconstruction has good post-operative results in terms of restoring stability, functional outcome and incidence of graft rupture. None of the studies have reported DB ACL reconstruction inferior to SB ACL reconstruction.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Compared with single-bundle ACL reconstruction, the double-bundle technique produced better Lachman and pivot-shift test results, KT arthrometry results and Tegner score after 3-12 years post operation (19). In most cases, double-bundle ACL reconstruction yielded significantly favorable results on KT arthrometry, pivot shift test and Lachman test (16)(17)(18)(19)(20)(21)(22)(23)(24), as well as reduced graft failure (22)(23)(24) and improved International Knee Documentation Committee (IKDC) objective score (18,23,24) compared with single-bundle ACL reconstruction. Therefore, double-bundle ACL reconstruction is indicated to be superior to single-bundle ACL reconstruction.…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, inferior outcomes to primary ACL reconstructions were reported, although significant improvements have been demonstrated after revision reconstruction (10)(11)(12)(13)(14). Of note, most revision ACL constructions were performed using a single-bundle technique (15); however, a vast amount of evidence has demonstrated that the double-bundle technique is superior to the single-bundle technique for primary ACL reconstruction (16)(17)(18)(19)(20)(21)(22)(23)(24). Compared with single-bundle ACL reconstruction, the double-bundle technique produced better Lachman and pivot-shift test results, KT arthrometry results and Tegner score after 3-12 years post operation (19).…”
Section: Introductionmentioning
confidence: 99%